Contributing to the scientific literature: citation analysis of CIFOR publications - Angelsen, A.; Aryal, B. (Center for International Forestry Research, 2005)
This study examines the frequency of citations of CIFOR publications in order to provide a useful indicator of CIFOR’s research impact. Out of the 1437 publications registered in CIFOR’s publication database up until May 2004, 24 % have been cited in scientific journals. Refereed articles make up 24% of CIFOR’s publications and have a 30-40 times greater likelihood of being cited than a refereed book or chapter. Forest Ecology and Management tops the list of most articles by CIFOR researchers (33) and citations of CIFOR work (170). The first author of about half of the most cited CIFOR publications are non-CIFOR researchers in joint authorship with CIFOR staff , indicating CIFOR and its scientists benefi t from partner collaboration. Th e study shows that CIFOR publications remain a useful reference and source of information for long periods, with no sign of falling citation rates even after 5-7 years. Less than 40 % of the citations appear within the fi rst four years of publication. Many papers appear in low impact journals, but with a bit more ‘upgrading’ many could have appeared in higher quality journals. While it is natural for many CIFOR papers to appear in forestry journals, the study also suggests CIFOR’s impact can be increased by publishing more papers in broader journals related to biology, ecology, conservation, social sciences, economics and development.